Environmental Cost and Firm Sustainability in Nigeria - Oluwayemisi , Ali-Momoh Betty; Olatunde, Ogundele Johnson; Joshua , Adegun Taiwo; Adejumoke, Braimoh Omotola; Alice, Ilo Oluwakemi; Kayode, Bejide Michael; David, Fabiyi Adekunle (Acta Universitatis Danubius. Œconomica, 2024)
This study aims to investigate the determinants of environmental costs in the manufacturing sector in Nigeria, focusing on the role of sustainable practices, regulatory compliance, and operational strategies.it specifically explored the mediating effect of sustainable practices on environmental costs for manufacturing firms in Nigeria and also assessed the moderating influence of regulatory compliance on the relationship between environmental costs and firm sustainability in the Nigerian manufacturing sector. Utilizing an ex-post facto design, this study examines environmental costs and sustainability practices among selected manufacturing companies in Nigeria. The population comprises sixty-six registered manufacturing firms listed on the Nigerian Stock Exchange as of December 31, 2021, with a minimum operational history of ten years. A sample of twenty-eight firms is randomly selected, and secondary data from annual reports spanning 2013 to 2023 are analyzed using descriptive statistics, correlation analysis, multicollinearity tests, panel regressions, and diagnostic evaluations. Descriptive statistics result revealed insights into the distributional characteristics of variables related to environmental costs and sustainability practices. The Pearson correlation matrix identifies significant correlations among variables, while the multicollinearity test confirms the absence of multicollinearity issues. Panel regression results indicate that sustainable practices positively influence environmental costs, while regulatory compliance alone may not significantly impact them. Efforts to mitigate environmental impacts and enhance operational efficiency show mixed effects on environmental costs. The study concludes that a holistic approach integrating sustainable practices, regulatory compliance, and operational efficiency is essential for managing environmental costs in the Nigerian manufacturing sector.